Queering Vulnerability: A Layered Bioethical Approach - Sudenkaarne Tiia (Finnish Anthropological Society, 2022)
Vulnerability is a concept often used in bioethics. However, it is seldom interrogated from a queer point of view. By queer inquiry, I refer to an umbrella understanding of gender and sexuality as diverse. In this article I discuss lesbian, gay, bisexual, trans, queer and intersex -related (LGBTQI) approaches to vulnerability. Framing these discussions from queer and LGBTQI bioethical theory, I offer an original approach to vulnerability based on queer bioethics and on a layered understanding of vulnerability. After considering queer bioethics and its (queer) critiques, I conclude that a layered understanding of vulnerability has strong potential for analyzing LGBTQI/queer vulnerabilities in bioethics. For further research, I formulate four layers of queer vulnerabilities to demonstrate some of that potential. I call these the layer of ethical sustainability, the layer of queer agency, the layer of interrogatory intimacy, and the layer of troubled kinship. I insist all layers should be critically evaluated and developed further with intersectional approaches.